During AMC testing, the AoPS Wiki is in read-only mode. No edits can be made.

Difference between revisions of "2019 USAMO Problems/Problem 1"

(Solution)
(Solution)
Line 4: Line 4:
 
==Solution==
 
==Solution==
  
<math>\newline</math>
+
 
 
Let <math>f^r(x)</math> denote the resulr when <math>f</math> is applied to <math>x</math> <math>r</math> times.
 
Let <math>f^r(x)</math> denote the resulr when <math>f</math> is applied to <math>x</math> <math>r</math> times.
 
<math>\hfill \break \hfill \break</math>
 
<math>\hfill \break \hfill \break</math>
If <math>f(p)=f(q)</math>, then <math>f^2(p)=f^2(q)</math> and <math>f^{f(p)}(p)=f^{f(q)}(q)\newline\implies p^2=f^2(p)\cdot f^{f(p)}(p)=f^2(q)\cdot f^{f(q)}(q)=q^2\newline\implies p=\pm q\newline\implies p=q</math> since <math>p,q>0</math>.
+
If <math>f(p)=f(q)</math>, then <math>f^2(p)=f^2(q)</math> and <math>f^{f(p)}(p)=f^{f(q)}(q)</math>
\newline
+
 
 +
<math>\implies p^2=f^2(p)\cdot f^{f(p)}(p)=f^2(q)\cdot f^{f(q)}(q)=q^2</math>
 +
 
 +
<math>\implies p=\pm q</math>
 +
 
 +
<math>\implies p=q</math> since <math>p,q>0</math>.
 +
 
 
Therefore, <math>f</math> is injective.
 
Therefore, <math>f</math> is injective.
<math>\newline\newline</math>
+
 
 +
 
 
Lemma 1: If <math>f^r(b)=a</math> and <math>f(a)=a</math>, then b=a.
 
Lemma 1: If <math>f^r(b)=a</math> and <math>f(a)=a</math>, then b=a.
<math>\newline\newline</math>
+
 
 +
 
 
Proof:
 
Proof:
<math>\newline</math>
+
 
 
Otherwise, set <math>a</math>, <math>b</math>, and <math>r</math> to a counterexample of the lemma, such that <math>r</math> is minimized. By injectivity, <math>f(a)=a\implies f(b)\neq a</math>, so <math>r\neq1</math>. If <math>f^n(b)=a</math>, then <math>f^n-1(f(b))=a</math> and <math>f(b)\neq a</math>, a counterexample that contradicts our assumption that <math>r</math> is minimized, proving Lemma 1.
 
Otherwise, set <math>a</math>, <math>b</math>, and <math>r</math> to a counterexample of the lemma, such that <math>r</math> is minimized. By injectivity, <math>f(a)=a\implies f(b)\neq a</math>, so <math>r\neq1</math>. If <math>f^n(b)=a</math>, then <math>f^n-1(f(b))=a</math> and <math>f(b)\neq a</math>, a counterexample that contradicts our assumption that <math>r</math> is minimized, proving Lemma 1.
<math>\newline\newline</math>
+
 
 +
 
 
Lemma 2: If <math>f^2(m)=f^{f(m)}(m)=m</math>, and <math>m</math> is odd, then <math>f(m)=m</math>.
 
Lemma 2: If <math>f^2(m)=f^{f(m)}(m)=m</math>, and <math>m</math> is odd, then <math>f(m)=m</math>.
<math>\newline\newline</math>
+
 
 +
 
 
Proof:
 
Proof:
<math>\newline</math>
+
 
Let <math>f(m)=k</math>. Since <math>f^2(m)=m</math>, <math>f(k)=m</math>. So, <math>f^2(k)=k</math>. <math>\newline f^2(k)\cdot f^{f(k)}(k)=k^2</math>.<math>\newline</math>
+
Let <math>f(m)=k</math>. Since <math>f^2(m)=m</math>, <math>f(k)=m</math>. So, <math>f^2(k)=k</math>. <math>\newline f^2(k)\cdot f^{f(k)}(k)=k^2</math>.
Since <math>k\neq0</math>, <math>\newlinef^{f(k)}(k)=k</math>
+
 
<math>\newline</math>
+
Since <math>k\neq0</math>, <math>f^{f(k)}(k)=k</math>
 +
 
 
<math>f^m(k)=k</math>
 
<math>f^m(k)=k</math>
<math>\newline</math>
+
 
 
<math>f^{gcd(m, 2)}=k</math>
 
<math>f^{gcd(m, 2)}=k</math>
<math>\newline</math>
+
 
 
<math>m=f(k)=k</math>
 
<math>m=f(k)=k</math>
<math>\newline</math>
+
 
 
This proves Lemma 2.
 
This proves Lemma 2.
<math>\newline\newline</math>
+
 
 +
 
 
I claim that <math>f(m)=m</math> for all odd <math>m</math>.
 
I claim that <math>f(m)=m</math> for all odd <math>m</math>.
<math>\newline</math>
+
 
 
Otherwise, let <math>m</math> be the least counterexample.
 
Otherwise, let <math>m</math> be the least counterexample.
<math>\newline</math>
+
 
 
Since <math>f^2(m)\cdot f^{f(m)}(m)</math>, either
 
Since <math>f^2(m)\cdot f^{f(m)}(m)</math>, either
<math>\newline</math>
+
 
(1) <math>f^2(m)=k<m</math>, contradicted by Lemma 1 since <math>f(k)=k</math>.
+
<math>(1) f^2(m)=k<m</math>, contradicted by Lemma 1 since <math>f(k)=k</math>.
<math>\newline</math>
+
 
(2) <math>f^{f(m)}(m)=k<m</math>, also contradicted by Lemma 1.
+
<math>(2) f^{f(m)}(m)=k<m</math>, also contradicted by Lemma 1.
<math>\newline</math>
+
 
(3) <math>f^2(m)=m</math> and <math>f^{f(m)}(m)=m</math>, which implies that <math>f(m)=m</math> by Lemma 2.
+
<math>(3) f^2(m)=m</math> and <math>f^{f(m)}(m)=m</math>, which implies that <math>f(m)=m</math> by Lemma 2.
 
This proves the claim.
 
This proves the claim.
<math>\newline\newline</math>
+
 
 +
 
 
By injectivity, <math>f(1000)</math> is not odd.
 
By injectivity, <math>f(1000)</math> is not odd.
 
I will prove that <math>f(1000)</math> can be any even number, <math>x</math>. Let <math>f(1000)=x, f(x)=1000</math>, and <math>f(k)=k</math> for all other <math>k</math>. If <math>n</math> is equal to neither <math>1000</math> nor <math>x</math>, then <math>f^2(n)\cdot f^{f(n)}(n)=n\cdot n=n^2</math>. This satisfies the given property.
 
I will prove that <math>f(1000)</math> can be any even number, <math>x</math>. Let <math>f(1000)=x, f(x)=1000</math>, and <math>f(k)=k</math> for all other <math>k</math>. If <math>n</math> is equal to neither <math>1000</math> nor <math>x</math>, then <math>f^2(n)\cdot f^{f(n)}(n)=n\cdot n=n^2</math>. This satisfies the given property.
<math>\newline</math>
+
 
 
If <math>n</math> is equal to <math>1000</math> or <math>x</math>, then <math>f^2(n)\cdot f^{f(n)}(n)=n\cdot n=n^2</math> since <math>f(n)</math> is even and <math>f^2(n)=n</math>. This satisfies the given property.
 
If <math>n</math> is equal to <math>1000</math> or <math>x</math>, then <math>f^2(n)\cdot f^{f(n)}(n)=n\cdot n=n^2</math> since <math>f(n)</math> is even and <math>f^2(n)=n</math>. This satisfies the given property.
<math>\newline</math>
+
 
  
  

Revision as of 21:06, 24 April 2019

Problem

Let $\mathbb{N}$ be the set of positive integers. A function $f:\mathbb{N}\to\mathbb{N}$ satisfies the equation \[\underbrace{f(f(\ldots f}_{f(n)\text{ times}}(n)\ldots))=\frac{n^2}{f(f(n))}\]for all positive integers $n$. Given this information, determine all possible values of $f(1000)$.

Solution

Let $f^r(x)$ denote the resulr when $f$ is applied to $x$ $r$ times. $\hfill \break \hfill \break$ If $f(p)=f(q)$, then $f^2(p)=f^2(q)$ and $f^{f(p)}(p)=f^{f(q)}(q)$

$\implies p^2=f^2(p)\cdot f^{f(p)}(p)=f^2(q)\cdot f^{f(q)}(q)=q^2$

$\implies p=\pm q$

$\implies p=q$ since $p,q>0$.

Therefore, $f$ is injective.


Lemma 1: If $f^r(b)=a$ and $f(a)=a$, then b=a.


Proof:

Otherwise, set $a$, $b$, and $r$ to a counterexample of the lemma, such that $r$ is minimized. By injectivity, $f(a)=a\implies f(b)\neq a$, so $r\neq1$. If $f^n(b)=a$, then $f^n-1(f(b))=a$ and $f(b)\neq a$, a counterexample that contradicts our assumption that $r$ is minimized, proving Lemma 1.


Lemma 2: If $f^2(m)=f^{f(m)}(m)=m$, and $m$ is odd, then $f(m)=m$.


Proof:

Let $f(m)=k$. Since $f^2(m)=m$, $f(k)=m$. So, $f^2(k)=k$. $\newline f^2(k)\cdot f^{f(k)}(k)=k^2$.

Since $k\neq0$, $f^{f(k)}(k)=k$

$f^m(k)=k$

$f^{gcd(m, 2)}=k$

$m=f(k)=k$

This proves Lemma 2.


I claim that $f(m)=m$ for all odd $m$.

Otherwise, let $m$ be the least counterexample.

Since $f^2(m)\cdot f^{f(m)}(m)$, either

$(1) f^2(m)=k<m$, contradicted by Lemma 1 since $f(k)=k$.

$(2) f^{f(m)}(m)=k<m$, also contradicted by Lemma 1.

$(3) f^2(m)=m$ and $f^{f(m)}(m)=m$, which implies that $f(m)=m$ by Lemma 2. This proves the claim.


By injectivity, $f(1000)$ is not odd. I will prove that $f(1000)$ can be any even number, $x$. Let $f(1000)=x, f(x)=1000$, and $f(k)=k$ for all other $k$. If $n$ is equal to neither $1000$ nor $x$, then $f^2(n)\cdot f^{f(n)}(n)=n\cdot n=n^2$. This satisfies the given property.

If $n$ is equal to $1000$ or $x$, then $f^2(n)\cdot f^{f(n)}(n)=n\cdot n=n^2$ since $f(n)$ is even and $f^2(n)=n$. This satisfies the given property.



The problems on this page are copyrighted by the Mathematical Association of America's American Mathematics Competitions. AMC logo.png

See also

2019 USAMO (ProblemsResources)
First Problem Followed by
Problem 2
1 2 3 4 5 6
All USAMO Problems and Solutions
Invalid username
Login to AoPS